Understanding Accounting Changes in an Efficient Market: Evidence of Differential Reaction . - Abdel-Khalik, A. Rashad; McKeown, James C. (The Accounting Review, 1978)
Abstract ABSTRACT: Using two samples (one as an experimental and one as a control), the authors evaluated the joint effect of two factors on the behavior of common stock prices. These factors were (1) the decision to switch the method of costing inventory to LIFO, and (2) the sign of the expected growth in EPS before the announcement of the change was made. The findings in this article appear to support the hypothesis that the decision to change the accounting method of costing inventory to LIFO is given different interpretations by the securities market, depending on the sign of expected growth in EPS. The significance of the joint effect of the two factors and the existence of differential reaction to the accounting change suggests that intervening variables mediate between accounting-based information and the securities market in processing of the signals provided by such information. Different intervening variables may alter the interpretation of the same accounting event.